Obstetric Outcome Following Bariatric Surgery in Kingdom of Bahrain - SUNDER, AMALA; Varghese , Bessy; Albuainain , . Haya; Bahzad , Noora; Talal Almehzaa , Reem; Mahmood butt , Maria; Darwish, Basma; Dayoub, Nawal (International Journal of Innovative Research in Medical Science, 2024)
Background: Obesity has complications in relation to health as well as pregnancy. Bariatric surgeries gain interest among obese women to reduce the adverse obstetric outcomes. However, pregnancy post bariatric surgeries have benefits as well as risks. The study analyzed the effects of bariatric surgery on pregnancy, delivery, and postpartum period. Method: This is a retrospective study conducted in Bahrain Defense Force Hospital from September 2019 till August 2020. The study included women in the reproductive age who had bariatric surgery before planning pregnancy and a control group of women who did not undergo the bariatric surgeries. Comparison of obstetric outcome was done between both groups. Data included demographic characteristics, method conceived, antenatal pathway, delivery process and postpartum period. Results were presented as odds-ratios (OR) with 95% confidence interval (CI) and P-values. P values of less than 0.05 were considered statistically significant. Result: This analysis includes 2972 patients. 47 patients of them had undergone previous bariatric procedure. Patients with previous bariatric surgery were older 32.8vs 29.9 and interestingly heavier with BMI 34.5 vs 31.1. Patients with previous bariatric surgery had more antenatal complications 36% vs 18.5%(p=0.002). The most evident complication is gestational diabetes with 21.3% of patients who had bariatric surgery developed Gestational Diabetes Mellitus(GDM) during pregnancy compared to 8.9% of patients without the surgery (P=0.004). Both groups had similar start of labor,1st stage of labor,2nd stage of labor, 3rd stage of labor and prolonged 2nd stage of labor. Caesarean section rate was similar at 42.6% vs35.4%(p=0.31). After adjusting confounding factors, previous bariatric surgery increased length of stay in hospital more than 3 days with OR 2.3 95%CI (1.2-4.4) P=0.01. Conclusion: Our study concluded the antenatal complications, Gestational diabetes as well as postpartum length of stay are significantly increased in post bariatric pregnant women. However, labor process and fetal outcome did not show significant difference.